The Technological Development of Decorated Corinthian Pottery, 8th to 6th Centuries BCE. Issue 1656 (16th October 2015) - Stephens, Jay A.; Vandiver, Pamela B.; Hernandez, Stephen A.; Killick, David
ABSTRACT: Polychrome slipped and decorated pottery from Corinth, Greece, developed over two centuries from monochrome, dark brown slips and washes on a calcareous yellow clay body to a wide range of decorative techniques. Once significant experimentation with color variability began, five colors, each with various levels of gloss, were produced. Some slip colors involve multiple-step processing to control glass content and degree of sintering; the control of particle size to produce variable roughness and a matte or semi-matt or glossy appearance. Considerable evidence supports nearly continuous development and engineering of the ceramic slips, although no data support the improvement in composition or processing of the ceramic bodies. For instance, significant macro-porosity consistently is present in the bodies. We present the results of study of 27 sherds with 59 examples of Corinthian polychrome paint layers, measuring 5 to 35 microns in thickness, that were collected by Marie Farnsworth in the late 1950s and 1960s from Greek archaeological sites. Black, red, white, wine red (or purple) and overlying, matte banded slips and paints were studied by optical microscopy, petrographic and scanning-electron microscopy with semi-quantative energy dispersive x-ray analysis, as well as wavelength-dispersive electron microprobe (EPMA) elemental mapping and analysis.